2001
DOI: 10.1152/ajpheart.2001.281.5.h2105
|View full text |Cite
|
Sign up to set email alerts
|

Chronic estrogen depletion alters adenosine diphosphate-induced pial arteriolar dilation in female rats

Abstract: We examined pial arteriolar reactivity to a partially endothelial nitric oxide synthase (eNOS)-dependent vasodilator ADP as a function of chronic estrogen status. The eNOS-dependent portion of the ADP response was ascertained by comparing ADP-induced pial arteriolar dilations before and after suffusion of a NOS inhibitor, N(omega)-nitro-L-arginine (L-NNA; 1 mM) in intact, ovariectomized (Ovx), and 17beta-estradiol (E2)-treated Ovx females. We also examined whether ovariectomy altered the participation of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 28 publications
8
31
3
Order By: Relevance
“…In confirmation of earlier results published from our laboratory (24,25), initial suffusions with ADP, at 10 and 100 M, elicited similar dosedependent vasodilations in intact (13.4 Ϯ 1.9% and 29.8 Ϯ 5.8%, respectively), Ovx (14.1 Ϯ 2.4% and 35.3 Ϯ 8.4%, respectively), and OVE (12.3 Ϯ 3.0% and 28.4 Ϯ 4.9%, respectively) females (Fig. 1).…”
Section: Effect Of Chronic Nos Inhibition On Adp-induced Vasodilationsupporting
confidence: 90%
See 2 more Smart Citations
“…In confirmation of earlier results published from our laboratory (24,25), initial suffusions with ADP, at 10 and 100 M, elicited similar dosedependent vasodilations in intact (13.4 Ϯ 1.9% and 29.8 Ϯ 5.8%, respectively), Ovx (14.1 Ϯ 2.4% and 35.3 Ϯ 8.4%, respectively), and OVE (12.3 Ϯ 3.0% and 28.4 Ϯ 4.9%, respectively) females (Fig. 1).…”
Section: Effect Of Chronic Nos Inhibition On Adp-induced Vasodilationsupporting
confidence: 90%
“…In intact and OVE groups, topical applications of L-NNA for 60 min combined with 10 mg/kg iv Indo resulted in 70% and 50% reductions in the vasodilations produced by 10 and 100 M ADP, respectively. These changes can be ascribed entirely to L-NNA, because it was previously shown that Indo alone has no effect on ADP reactivity in the same female groups (25). Chronic L-NAME treatment affected ADP responses in a manner similar to that observed in vehicle control rats after acute topical application of a NOS inhibitor (L-NNA).…”
Section: Effect Of Chronic Nos Inhibition On Adp-induced Vasodilationmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, estrogens, which are known to modulate gap junctional communication, have been reported to upregulate the EDHF phenomenon in peripheral vessels 39 but to depress EDHF-type relaxations in cerebral arteries. 6,40 Indeed, in pial arterioles 37,43 Gap27 attenuates the endothelium-dependent component of ADP-induced dilation in ovariectomized rats but not in control rats. 36 Finally, there may be significant regional variations in connexin expression in intracerebral arteries from the same species.…”
Section: Ujiie Et Al Gap Junctions and Relaxation In Cerebral Arteriementioning
confidence: 96%
“…Although less well documented, agonists such as acetylcholine (ACh), ATP, and substance P also stimulate EDHF-type relaxations in isolated cerebral vessels, including human vessels, [1][2][3][4][5][6] and analogous responses have been observed in the pial microcirculation in vivo. 6 EDHF-type relaxations appear to play a more prominent role in small branch arteries and arterioles from peripheral beds and the intracerebral vasculature than in major supply vessels, whereas the importance of NO-mediated relaxations may diminish progressively along the vascular tree. 4,7 Such observations suggest that the EDHF phenomenon may be a significant determinant of microvascular resistance and cerebral perfusion under physiological conditions.…”
mentioning
confidence: 99%